Women's Perception of Sexuality and Sexual Violence in Turkish Culture - Are Women Aware of This Difficult Distinction?: A Qualitative Research - Ebru Cirban Ekrem; Aylin Kurt (Genel Tıp Dergisi)

(untitled)
Background/Aims: We aimed to determine the perceptions of women living in the Turkey whether they live their sexual life in line with their sexual desires or as sexual violence. Methods: This qualitative study was carried out with 18 women by in-depth interviews. In-depth and semi- structured interviews were conducted between December 2021- July 2022. Content analysis was used for data analysis. Results: Three themes were identified in the study: (1) the building block of marriage (2) sexuality as violence (3) the effects of sexual violence. The participants emphasized that their different expressions of sexuality from their groups, when they do not feel sexual desire, the sexual function is an act of violence in which the woman is the object of sex. Sexual harassment, some women were also exposed to verbal and psychological violence of a sexual nature. Conclusion: At the end of the study, it was determined that women saw sexuality as a fundamental element for the continuation of marriage and commitment to their spouse. Participants stated that they were occasionally exposed to sexual violence and different types of violence.